2009
DOI: 10.1021/ac8023262
|View full text |Cite
|
Sign up to set email alerts
|

Development of Enantioselective Polyclonal Antibodies to Detect Styrene Oxide Protein Adducts

Abstract: Styrene has been reported to be pneumotoxic and hepatotoxic in humans and animals. Styrene oxide, a major reactive metabolite of styrene, has been found to form covalent binding with proteins, such as albumin and hemoglobin. Styrene oxide has two optical isomers and it was reported that the (R)-enantiomer was more toxic than the (S)-enantiomer. The purpose of this study was to develop polyclonal antibodies that can stereoselectively recognize proteins modified by styrene oxide enantiomers at cysteine residues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…The purified scFv G11 antibody was subsequently used to evaluate performance by an indirect competitive ELISA. Prior to ELISA, the optimal concentration of coating antigen and dilutions of scFv were determined by a checkerboard assay. , To evaluate the potential interferences that may be encountered, for example, in human urine samples, it was necessary to study the effects of pH and ionic strength on the ELISA. As shown in Figure A, the ELISA was more sensitive under neutral and slightly alkaline conditions than under slightly acidic ones.…”
Section: Resultsmentioning
confidence: 99%
“…The purified scFv G11 antibody was subsequently used to evaluate performance by an indirect competitive ELISA. Prior to ELISA, the optimal concentration of coating antigen and dilutions of scFv were determined by a checkerboard assay. , To evaluate the potential interferences that may be encountered, for example, in human urine samples, it was necessary to study the effects of pH and ionic strength on the ELISA. As shown in Figure A, the ELISA was more sensitive under neutral and slightly alkaline conditions than under slightly acidic ones.…”
Section: Resultsmentioning
confidence: 99%
“…7,19 However, the prepared enantioselective antibody oen had crossreactivity to distomer, and it indicated that the antibody could still recognize distomer in some extent. [20][21][22] For example, the Sibuprofen antibody still had more than 50% cross-reactivity to the R-enantiomer. 20 Enantioselective antibodies had the ability to recognize the distomer, which would restrict the application of antibodies in the eld of chiral drug separation and detection.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, enantioselective immunoassay research has arisen in chiral compounds analysis, since it displays high sensitivity [8], simplicity [9], low cost [10], and high throughput [11]. At the same time, several enantioselective antibodies against small molecules have emerged [9][10][11][12]. However, the stratagem of immunogen design and enantioselective antibody preparation for amlodipine or other dihydropyridines has not been revealed.…”
Section: Introductionmentioning
confidence: 99%